PERKEMBANGAN TENUN SIAK DARI MASA KE MASA (1926-2015) - Anisa Mutiara Priyadi; Isjoni Isjoni; Kamaruddin Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract : Weaving Siak is rooted and becomes part of the local culture. In addition, this weaving also plays an important role in the development of cultural treasures of the nation because it is a real cultural repertoire. The purpose of this research is to find out when the beginning of entry of weaving to Siak area, to find out the factors behind the development of weaving Siak, to find out how the development of weaving Siak from time to time (1926-2015), which include: manufacturing technique, motif, type, function. The method used in this research is qualitative. Data obtained from the interviews are then analyzed by the language it self. The research was started since the beginning of the title of the researcher submitted until the completion of this thesis. Data collection techniques used are observation techniques, interview techniques, and literature study techniques. The results showed that the development of weaving Siak backed by several factors, that is: improved human civilization, community appreciation, customs and culture, economy, and government support. The manufacture technique of woven fabric was starting to use tumpu weaving equipment, kik, and non machine weaving equipment (manual). Siak weaving motif comes from flora, fauna, and certain forms. Weaving Siak has undergone much development, not only as clothing and social functions but also as aesthetic and economic objects.Keywords : Weaving Siak, Culture, Development